Avaliação da Vanillosmopsis arborea Baker e (-)-α-bisabolol frente a parâmetros oxidativos e toxicológicos - Leite, Gerlânia de Oliveira (2017)
Vanillosmopsis arborea Baker belongs to the Asteraceae family and has a recognized economic value due to its anti-inflammatory properties, derived from sesquiterpene (-)-α-bisabolol (BISA), which is present in high concentrations in the essential oil of its wood (OEVA). BISA is used in a wide variety of dermatological products. Some studies suggest that the pharmacological effects of this sesquiterpene, as well as the OEVA, may be related to its antioxidant activity. Rotenone, a pesticide which acts as mitochondrial inhibitor of the complex I from electron chain transporter, has been used in experimental models of parkinsonism by causing an increase in the production of reactive oxygen species (ROS). The aim of this study was to evaluate the antioxidant activity of V. arborea, as well as the antioxidant, neuroprotective and toxicological potential of (-)-α-bisabolol in different experimental models. Firstly, it was evaluated the in vitro effect of the OEVA and the extract of de V. arborea on the Fe (II)-induced thiobarbituric acid (TBARS) production and dichlorofluorescein (DCFH) oxidation in rat brain homogenates, the antioxidant potential through the DPPH radical scavenging test (2 , 2-diphenyl-1-picrylhydrazyl) and the chelating activity. The extracts of V. arborea presented antioxidant activity in vitro demonstrated through a decrease in lipid peroxidation induced by Fe(II), and by its ability in to scavenging DPPH radical. Moreover, the OEVA and BISA reduced the oxidation of DCFH induced by H2O2.The effect of BISA was also in a model of cytotoxicity and genotoxicity in peripheral blood mononuclear (PBMC) and red blood cells from humans. The BISA reduced the cellular viability, caused a nuclear damage and hemolytic activity only when the cells were exposed to high concentrations. After, the antioxidant and neuroprotective effect of BISA was evaluated in vivo using Drosophila melanogaster as organism model. The fruit flies were exposed to rotenone and/or BISA and it were observed behavioral parameters using negative geotaxis and mortality tests. In this model, it were also determined the expression of genes of superoxide dismutase (SOD), catalase and Keap 1 (related to the oxidative stress signaling pathway), also the thiol content and mitochondrial I complex activity. BISA showed no toxicity in the D. melanogaster model. BISA decreased the mortality and increased the locomotor activity in D. melanogaster exposed to rotenone. The alteration in the expression of SOD mRNA caused by rotenone was normalized by treatment with BISA (250 μM). BISA did not change the other parameters tested. In conclusion, V. arborea presents antioxidant activity. BISA, the main constituent of the essential oil, demonstrated antioxidant and neuroprotective activity, besides not showing toxicity in an experimental model using D. melanogaster. The cytotoxicity and genotoxicity of this compound was observed only at high concentrations and over a long period of exposure to PBMC. Therefore, our results show that BISA protects against the toxicity induced by rotenone. Our study reports the antioxidant, neuroprotective effects of V. arborea and its major compound, with low toxicity and suggests its potential as a possible therapeutic agent.